Normalizing Transantiago: On the challenges (and limits) of repairing infrastructures. (June 2014) - Ureta, Sebastián
This article looks to propose a new way to understand the repair of failing large sociotechnical systems. Leaving aside romantic valuations, repair always involves a certain degree of normalization. Derived from conceptualizations by Foucault, repair as normalization is understood as a particular form of power that, first, recognizes a certain normal state to which the failing system should evolve and, second, develops different strategies to reach it, usually involving the deployment of particular disciplinary devices. The ultimate aim of such practices is usually not only the improvement of the system but centrally the maintenance of a certain kind of power. In order to show the empirical usability of such conceptualization, the article analyzes the case of Transantiago, a thoroughgoing reform of the public transport system of Santiago, Chile. The start of Transantiago in February 2007 was marred by multiple failures, becoming one of the biggest public controversies in the country in recent decades. Given this, several different strategies were developed to repair such failures, understanding them explicitly as normalization. The article analyzes two particular strategies: attempts to change the negative 'public perception' about Transantiago through the use of quantitative indicators and the introduction of an unexpected type of infrastructure to increase the overall speed of the system. Finally, the conclusion analyzes how the conception of repair as normalization can help us better understand the complexities involved in dealing with failing large sociotechnical systems such as Transantiago, pointing to the need to sometimes move beyond repair .